Distinguishing Radix Angelica sinensis from different regions by HS-SFME/GC–MS. (1st November 2015) - Tan, Hong-Sheng; Hu, Dong-Dong; Song, Jing-Zheng; Xu, Yong; Cai, Shuang-Fan; Chen, Qi-Long; Meng, Qian-Wan; Li, Song-Lin; Chen, Shi-Lin; Mao, Qian; Xu, Hong-Xi
Highlights: A HS-SFME based GC–MS was developed for discriminating RAS from different regions. Potential characteristic markers of RAS from top-geoherb region were revealed. Fifty-one VOCs were identified. Sulphur-fumigation might be the reason for the quality inconsistencies of RAS samples. Abstract: An automated headspace solvent free microextraction (HS-SFME) based gas chromatography/mass spectrometry (GC/MS) was developed for discrimination of Radix Angelica sinensis (RAS) from different cultivation regions. The MS data were subjected to principal component analysis (PCA) and hierarchical clustering analysis (HCA) to rapidly find the potential characteristic components of RAS from top-geoherb region and non top-geoherb region. Totally, fifty-one volatile organic compounds (VOCs) were identified, in which β -ocimene, α -pinene, 3-methylbutanal, heptanes, butanal were identified as potential markers for distinguishing RAS from top-geoherb region and non top-geoherb region. Sulphur dioxide was detected in some commercial RAS samples, which implied that sulphur-fumigation might be the main reason for the quality inconsistencies of commercial RAS samples. These results suggested that RAS from top-geoherb region and non-top geoherb region could be discriminated by the method. And characteristic chemical markers found in current study can be used for ensuring consistent quality of top-geoherb of RAS.